Why and How to Treat Chronic Hepatitis C - Stephanos J Hadziyannis (Canadian Journal of Gastroenterology)
Chronic hepatitis C (CHC) is a major health problem worldwide, with approximately 200 million affected individuals and a significant rate of progression to end-stage cirrhosis and hepatocellular carcinoma (HCC). If hepatitis C virus (HCV) infection is left untreated in the population, then the number of liver-related deaths will soon double and the need for liver transplantation may increase to five times that seen today. Available therapies for CHC are restricted to interferon alpha (IFN-α ) monotherapy and to the combination of IFN-α and ribavirin. Despite their high cost and side effects, both of these therapies have proved to be cost effective, particularly combination therapy. IFN-α monotherapy for one year can induce sustained response (SR) rates of approximately 10% in naive patients infected with HCV genotype 1, and above 50% in those infected with other genotypes. Combination therapy can double or even triple the rate of SR in genotype 1 infections and may further increase the SR rate in the other HCV genotypes. Combination therapy has also been proven to be effective in approximately 50% of relapsed responders to IFN-α monotherapy. In clinical practice, the decision to treat should be individualized and tailored on the basis of several virus- and host-related factors, particularly the grade and stage of liver disease, HCV genotype and levels of viremia. Appropriate monitoring of therapy by careful clinical evaluation, liver biochemistry and serumHCVRNAtesting is mandatory. IFN-α therapy may also prove to be effective in reducing the rate of HCC development in CHC regardless of whether a virological response is achieved, but this remains to be established.